AMAMENTAÇÃO: RELATOS DAS VIVÊNCIAS DE MULHERES CAMPONESAS DE UM MUNICÍPIO DO SUDOESTE PARANAENSE - KEIL, MARINA JOICE (2021)
This research aims to understand the breastfeeding experience of mothers peasant women from Capanema (PR), still aiming to identify knowledge and practices involving breastfeeding of lactating women and understand their perception of the act of breastfeeding within their social organization and in the field work. The research used Thematic Oral History methodology for construction and analysis of the speeches, because in this one, listening to the mothers is privileged. The construction of the research used the qualitative approach and uses the interview as a basis for the dialogue half structured. Fieldwork was carried out in the mothers' homes. peasants or via WhatsApp video call. Through dialogue with five farming mothers who are breastfeeding, it is possible to identify their relationship with work in the field and the experience of motherhood with emphasis on breastfeeding in the context of the Covid-19 pandemic.